Pengaruh Pendidikan Kesehatan Pada Tingkat Pengetahuan Ibu Post Partum Tentang Senam Nifas - Meta Nurbaiti (Ilmiah Institut Citra Internasional, 2023)
One of the ways to keep uterine contractions healthy is simple exercise, the exercise that can be used is postpartum exercise. Because with postpartum exercise, the muscles in the uterus will experience contractions and retractions which with these contractions will cause the blood vessels in the uterus to stretch to get pinched so that bleeding can be avoided. The purpose of this study was to determine the effect of health education on the level of knowledge of post partum mothers about postpartum exercise. The research design used was the one group pre test and post test only design approach. The sample in this study were post partum mothers as many as 32 people. Samples taken by total sampling. The results of this study were analyzed using bivariate analysis using the Wilcoxon test. The results of this study indicate that the distribution of the frequency of knowledge of post partum mothers before being given health education is mostly less knowledgeable, namely as many as 20 sampelts (62.5%). The distribution of the frequency of knowledge of post partum mothers after being given health education is mostly good knowledge, namely 28 sampelts (87.5%). Wide gap in knowledge post partum mothers before and after health education with a p value of 0.002 (<0.05). It is hoped that there will be more education for post partum mothers about the benefits of postpartum exercise.